Diagnostic value of myocardial strain analysis for the detection of significant coronary artery disease. - Amel Valiente Turro; Giselle Coutin Marie; Julio Oscar Cabrera Rego; Raymid García Fernández; Jany Rodríguez Londres; Juan Valiente-Mustelier (ECIMED, 2012)
Introduction Myocardial strain, a new derived technique of the tissue Doppler, arises as a need to perfect the segmental analysis of the contractilefunction of the heart based on images of high resolution.Objective To determine the utility of myocardial strain as a non invasive method for the diagnosis of significant coronary artery disease by invasivecoronary angiography in patients with high suspicious of coronary artery disease.Method A prospective descriptive and cross-sectional study was conducted between September 2008 and August 2009. We included 50 patientswho underwent invasive coronary angiography, with previous transthoracic echocardiography exam to assess the longitudinal strain of thedifferent segments of the left ventricle, excluding those with dual irrigation to avoid false positives. We determined sensitivity, specificity,positive and negative predictive value, as well as the area under the curve ROC for the different myocardial strain parameters in the detectionof significant coronary artery disease.Results The peak strain showed high sensitivity (90,1%) and negative predictive value (90,3%) while the postsystolic strain index had a higherspecificity (95,1%) and positive predictive value (89,5%), with an area under the curve (ROC) of 0,82.Conclusions The myocardial strain analysis by tissue Doppler image has an adequate diagnostic value for the detection of significant coronary arterydisease in patient with chronic stable angina